The Theory and Practice of Capital Structure: A survey of Libyan Companies - Buferna , Fakher Buferna (Dirasat in Economics and Business, 2005)
The mainstream approach in most previous empirical studies of capital structure has been to estimate regression equations w ith proxies for dependent and independent variables. These stu dies test for relationships betw een leverage variables and other factors. This methodology, how ever, has been criticised by Hem pel (1983) among others, because the explanatory variables are restricted to those which can be quantified. Barton and Gord-on (1987) argue that this restrict-tion leads to oversimplification of how the firm works. This quanti tative analysis tends to ignore managerial preferences in capital structure decisions, and Barton and Matthews (1989) state that a new paradigm is needed which includes the qualitative factors which have an impact on the firm's financing decisions.